Correction. Issue 1 (2nd January 2022) - Unknown
Abstract : Jalalain Daghigh A, Sadegh Kenevisi M, Mohd Jan J. 2021. Translation and feminism in post-Islamic revolution Iran: A sociological approach. Southern African Linguistics and Applied Language Studies . Advance online publication. https://doi.org/10.2989/16073614.2021.1935283 First author name and affiliation The first author's second name is spelled incorrectly. Jalalain should be Jalalian. The first author's affiliation is Universiti Malaya . The first sentence of the abstract With the 1979 Islamic revolution in Iran, the pre-revolution secular modernisation process was interrupted and, as believed by the liberal activists, the Islamisation of rules and domination of political Islamic views in the society-imposed restrictions on Iranian women increased. should be replaced with the following With the 1979 Islamic revolution in Iran, the pre-revolution secular modernisation process was interrupted and, as believed by the liberal activists, the Islamisation of rules and domination of political Islamic views in the society imposed restrictions on Iranian women.